Understanding Multiculturalism Education from Indonesia, Singapore, Malaysia, and Thailand - Yuyun Elizabeth Patras; Rais Hidayat; Arifin Maksum; Nina Nurhasanah (Universitas Kristen Satya Wacana, 2022)
Every nation faces increasingly complex challenges. Differences every day meet us. The purpose of this study is to learn from the implementation of multicultural education in four countries. This study uses a qualitative approach with content analysis techniques. The data source comes from 12 English articles obtained from scopus.com with the keywords